Applicability study of a low cost seismic isolator prototype using recycled rubber - Muñoz, Andre (2019)
In order to protect buildings against earthquakes that are categorized as "common" according to the Peruvian Earthquake Resistant Standard, a prototype of Recycled Rubber Seismic Isolator ("RRSI") was developed in the structural laboratory of the Japan-Peru Center for Earthquake Engineering Research and Disaster Mitigation - CISMID, Peru. The raw material used to manufacture this device was recycled rubber tires; the rubber tire was cut into square shape sheets with 190mmx190mm of cross-section and a total thickness of around 11 mm. Rubber tire sheets were joined to each other by a vulcanization process, including rubber layers with 3mm of thickness made of recycled rubber tire powder in between rubber tire sheets; and in between the rubber tire sheet and the steel plate at both ends of the bearing. Two specimens were tested in a shaking table under a free vibration impulse or displacement in order to get their natural vibration frequency, natural period, and inherent damping. Then, to obtain the hysteretical behavior, a cyclic lateral reversal-loading test was conducted on three different specimens applying a constant axial load of 330MPa, 270MPa, and 220MPa respectively and a lateral displacement pattern with different levels of shear deformations up to the failure, which occurs at a shear strain of around 100%. From the experimental results, a nonlinear hysteretic behavior and energy dissipation were observed, decoupling the lateral movement. Finally, a numerical model was proposed to model the nonlinear hysteretic behavior of the RRSI based on a Modified Bouc-Wen model. This numerical model was simulated by using the specimens as base isolators for buildings.